Agency in educational language planning: perspectives from higher education in Tunisia. Issue 1 (15th March 2021) - Badwan, Khawla
ABSTRACT: Post-modern approaches to language policy have emphasised the role of agency in implementing and appropriating language policies. While agency is often perceived in positive terms, Liddicoat [(2019). Constraints on agency in micro-language policy and planning in schools. In J. Bouchard & G. P. Glasgow (Eds.), Agency in language policy and planning: Critical inquiries (pp. 149–170). New York: Routledge.] calls on language policy researchers to investigate its problems and constraints. This article discusses the interplay of structure and agency in educational language policies in Tunisian higher education, a sector characterised by a 'benign neglect' approach to language policy. While doing so, it responds to Fenton-Smith and Gurney's [(2016). Actors and agency in academic language policy and planning. Current Issues in Language Planning, 17 (1), 72–87] observation that higher education contexts remain largely underexplored in the language policy scholarship. The article uses data from 12 semi-structured interviews from local higher education stakeholders in order to explore how their agency is exercised, rejected and contested. The study demonstrates that while agency creates room for flexibility and the ability to respond to changing local demands and aspirations, it can also cause problems such as inconsistency, uncertainty, and the reproduction of social inequalities.